Stable Isotope Ratio Analysis for Assessing the Authenticity of Food of Animal Origin. Issue 5 (19th July 2016) - Camin, Federica; Bontempo, Luana; Perini, Matteo; Piasentier, Edi
Abstract: The main elemental constituents (H, C, N, O, and S) of bio‐organic material have different stable isotopes ( 2 H, 1 H; 13 C, 12 C; 15 N, 14 N; 18 O, 17 O, 16 O; 36 S, 34 S, 33 S, and 32 S). Isotopic ratios can be measured precisely and accurately using dedicated analytical techniques such as isotope ratio mass spectrometry (IRMS). Analysis of these ratios shows potential for assessing the authenticity of food of animal origin. In this review, IRMS analysis of food of animal origin and variability factors related to stable isotope ratios in animals are described. The study also lists examples of application of stable isotope ratio analysis to meat, dairy products, fish, and shellfish and emphasizes the strengths and weaknesses of the technique. Geographical, climatic, pedological, geological, botanical, and agricultural factors affect the stable isotope ratios (SIR) of bio‐elements, and SIR variations are ultimately incorporated into animal tissue through eating, drinking, breathing, and exchange with the environment, being recorded in the resulting foods. SIR analysis was capable of determining geographical origin, animal diet, and the production system (such as organic/conventional or wild/farmed) for pork, beef, lamb, poultry, milk, butter, cheese, fish, and shellfish. In the case of the hard PDO (protected designations of origin) cheeses Grana Padano and Parmigiano Reggiano it is also used in real‐life situations to assess the authenticity of grated and shredded cheese on the market.